The human past : world prehistory and the development of human societies - Scarre, Christopher
The Human Past has established itself as a thorough and authoritative survey of human prehistory and the development of civilizations. Written by an international team of respected experts in the field, it presents a streamlined overview that can be broken down into a series of chapters focusing on individual regions and time periods. The Fourth Edition has been completely revised with key theme feature boxes, a new chapter on the peopling of the Americas, a section on methods and theories, full-color maps, timelines, illustrations, new coverage of sites and discoveries, and a fully updated e-media package, including all images from the book, test questions, and videos.